Corporate Social Responsibility and Consumer Behavior in Denmark - Larsen, Alma (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to analyze the corporate social responsibility and consumer behavior in Denmark Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The Danish study on CSR and consumer behavior shows that Danish consumers prefer socially responsible companies, willing to pay more for products/services from such firms. However, awareness and importance of CSR vary among demographic groups, highlighting the need for tailored strategies. Overall, prioritizing CSR can help companies differentiate themselves and attract loyal customers in Denmark's competitive market. Unique Contribution to Theory, Practice and Policy: Social identity theory, stakeholder theory & norm activation theory may be used to anchor future studies on analyze the corporate social responsibility and consumer behavior: a comparative study between Denmark. Companies operating in Denmark should prioritize the integration of authentic and transparent CSR initiatives into their business strategies. Government agencies in Denmark can play a crucial role in promoting CSR adoption and accountability among businesses.